DARI PASIF KE AKTIF: IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK DAN MIND MAPPING DALAM MENGEMBANGKAN PSIKOMOTORIK PESERTA DIDIK SEKOLAH DASAR - Zanna Khairatu Nisya; Dwitalia Sari, Dessy; Annisa, Muhsinah; Jannah, Fathul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research is that students experience difficulties in learning activities, which impacts their low ability to understand reading texts and express thoughts logically, as well as challenges in developing skills. Therefore, learning innovation is needed through a combination of Mind Mapping, Project Based Learning (PjBL), and Cooperative Learning models, aimed at describing teacher activities and analyzing improvements in student activities and psychomotor skills for second-grade students at SDN Pasar Lama 1 Banjarmasin. This research employs a qualitative and quantitative approach using Classroom Action Research (PTK), conducted over four meetings in the 2024/2025 academic year. The research subjects consist of 29 students. Data were collected through observations of teacher activities, student activities, and psychomotor skills, as well as written tests for quantitative data. Data analysis was performed using percentages and predetermined learning completion indicators. The results show that teacher activities in each meeting were carried out in the